2018
DOI: 10.3892/etm.2018.6395
|View full text |Cite
|
Sign up to set email alerts
|

A meta‑analysis on anterior cruciate ligament reconstruction: Is modified transtibial technique inferior to independent drilling techniques?

Abstract: This report respectively compared the standard transtibial (sTT) technique to the independent drilling (ID) techniques applied to anterior cruciate ligament (ACL) reconstruction. It also made a comparison between the clinical results of the modified transtibial (mTT) technique and of the ID techniques. Prospective studies on transtibial (TT) and ID techniques for ACL reconstruction were retrieved from several databases and a subgroup analysis was performed to compare the sTT technique with the ID techniques an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, several studies have demonstrated that the graft bending angle after the TP technique could be more acute than that after the TT technique, resulting in potential increase in mechanical stress around the bone tunnel orifice [ 10 13 , 16 , 28 , 46 ]. Since recent meta-analaysis demonstrated that the comparison between the modified TT and the TP technique demonstrated no significance difference in the clinical outcomes including anteroposterior and rotational stabilities [ 47 ], other factors rather than the kinematic stability of postoperative knee need to be elucidated to determine the optimal ACL reconstruction technique. Hence, we focused the stress patterns arising in the femoral bone, which were not well investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated that the graft bending angle after the TP technique could be more acute than that after the TT technique, resulting in potential increase in mechanical stress around the bone tunnel orifice [ 10 13 , 16 , 28 , 46 ]. Since recent meta-analaysis demonstrated that the comparison between the modified TT and the TP technique demonstrated no significance difference in the clinical outcomes including anteroposterior and rotational stabilities [ 47 ], other factors rather than the kinematic stability of postoperative knee need to be elucidated to determine the optimal ACL reconstruction technique. Hence, we focused the stress patterns arising in the femoral bone, which were not well investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of other analyses conflict with that contention, showing AM superiority with higher proportions of negative Lachman and pivot–shift tests, and better Lysholm and International Knee Documentation Committee (IKDC) scores [6, 11, 30, 50]. Other reviews offer a more mixed picture, with AM providing superior IKDC subjective scores but similar IKDC objective scores and pivot–shift test, Lachman test, Lysholm, and Tegner activity scale scores [53]. In terms of graft failure, research has shown mixed results, with some studies suggesting no correlation between AM and TT techniques and others showing higher failure with AM technique [10, 38, 44, 45, 51].…”
Section: Discussionmentioning
confidence: 99%